Financial strategies for a small company in Latin America to face a pandemic: a SME case in Peru - Loloy Huaringa, Diego Fernando (2023)
In this document is carried out at first, a literature investigation about the economic impact produced by a pandemic and the financial strategies recommended by numerous authors in order to summarize the main economic consequences of a pandemic and the principal financial strategies to face them. Subsequently, using methodological tools, such as questionnaires and direct observation, are tested the efficiency of this financial strategies in a small and medium enterprise (SME) in Peru, to then expand the results by applying the tool in a reduced version to other SMEs in different sectors in Latin America. Although the study showed interesting results for these particular cases, these are insufficient to provide a general rule for a large number of companies; however it offers a useful tool for finance managing in SME and could be used as a astarting point for future research related to this topic.